2010
DOI: 10.1245/s10434-010-1063-7
|View full text |Cite
|
Sign up to set email alerts
|

Limited Value of Staging Squamous Cell Carcinoma of the Anal Margin and Canal Using the Sentinel Lymph Node Procedure: A Prospective Study with Long-Term Follow-Up

Abstract: BackgroundSelection of patients with anal cancer for groin irradiation is based on tumor size, palpation, ultrasound, and fine needle cytology. Current staging of anal cancer may result in undertreatment in small tumors and overtreatment of large tumors. This study reports the feasibility of the sentinel lymph node biopsy (SLNB) in patients with anal cancer and whether this improves the selection for inguinal radiotherapy.MethodsA total of 50 patients with squamous anal cancer were evaluated prospectively. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 25 publications
0
21
0
1
Order By: Relevance
“…To better diagnose inguinal MTS, in recent years, SLNB has proven to be a safe and an effective technique (Spratt, 2000; Keshtgar et al , 2001; Vajda et al , 2001; Mistrangelo et al , 2002; Peley et al , 2002; Rabbit et al , 2002; Bobin et al , 2003; Damin et al , 2003; Ulmer et al , 2003; Castro et al , 2005; Damin et al , 2006; Gretschel et al , 2008; Mariani et al , 2008; Mistrangelo et al , 2009a; De Jong et al , 2010; Hirche et al , 2010; De Nardi et al , 2011). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To better diagnose inguinal MTS, in recent years, SLNB has proven to be a safe and an effective technique (Spratt, 2000; Keshtgar et al , 2001; Vajda et al , 2001; Mistrangelo et al , 2002; Peley et al , 2002; Rabbit et al , 2002; Bobin et al , 2003; Damin et al , 2003; Ulmer et al , 2003; Castro et al , 2005; Damin et al , 2006; Gretschel et al , 2008; Mariani et al , 2008; Mistrangelo et al , 2009a; De Jong et al , 2010; Hirche et al , 2010; De Nardi et al , 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in 2010, De Jong et al (2010) reported a limited value of staging squamous cell carcinoma of the anal margin and canal using the sentinel node procedure in a prospective study with long-term follow up. The authors conclude that, because of the occurrence of inguinal lymph node MTS after a tumour-negative SLNB, the introduction of this procedure as a standard of care in all patients with anal carcinoma should be done with caution to avoid undertreatment of patients who otherwise would benefit from inguinal radiotherapy.…”
mentioning
confidence: 99%
“…The draining sentinel nodes have been detectable in 66-100% of cases [57]. Lymph node metastases are found in 7.1-42% of patients [57,58] with false-negative rates of 3.7% [58,59].…”
Section: Stagingmentioning
confidence: 99%
“…En effet, à ce jour, un nombre limité de séries comportant de faibles effectifs de malades a été publié (193 cas au total) alors que la technique a commencé à se développer en 2002 [1][2][3][4][5][6][7][8][9]. Les résultats de ces séries sont résumés dans le tableau 1.…”
Section: Sentinel Lymph Node Anal Canal Carcinomaunclassified